The role of external beam radiation therapy in the management of thyroid carcinomas: A retrospective study in Iran Cancer Institute. Issue 1 (12th June 2022) - Esmati, Ebrahim; Aleyasin, Alireza; Ghalehtaki, Reza; Jafari, Fatemeh; Farhan, Farshid; Aghili, Mahdi; Haddad, Peiman; Kazemian, Ali
Abstract: Background: Thyroid cancers are histologically classified into three types; differentiated thyroid carcinoma (DTC), medullary thyroid carcinoma (MTC), and anaplastic thyroid carcinoma (ATC). Among the several therapeutic strategies for treatment and management of thyroid cancer, surgical resection in combination with radioactive iodine therapy (RAI) is indicated for moderate to high‐risk differentiated thyroid cancer (DTC) patients‐ according to current guidelines. However, external radiation therapy (EBRT) can be a viable alternative treatment option for these patients and scarce evidence is available regarding the efficacy and effectiveness of EBRT on thyroid cancer. Aim: This study aims at evaluating the role of EBRT in the management of thyroid carcinomas. Methods and Results: In this retrospective cohort study, the records of 59 patients with thyroid cancer were accessed who were treated by EBRT from 2008 to 2016. The indications for EBRT included unresectable primary (definitive) or loco‐regional recurrences (salvage) not suitable for RAI, palliation for local disease or metastatic foci (palliative), and the adjuvant treatment for suspected residual disease following resection. Progression‐free survival (PFS) and overall survival (OS) were calculated for different types of cancer. PFS was measured from the start of EBRT to the last uneventful follow‐up, recurrence, or death. Kaplan–Meier model was used for the survival analysis. Fifty‐nine patients were evaluated. The histopathology of the tumors was differentiated and poorly‐differentiated, medullary and anaplastic thyroid carcinomas in 22 and 6, 15 and 16 patients, respectively. Twenty‐seven patients received external beam radiotherapy (EBRT) as adjuvant therapy and 18 of the cases as palliative therapy while the remaining received salvage or definitive primary EBRT. The stage of patients' cancer was as follows: stage II in 3 and III in 1, IVA in 18 and IVB in 18 and IVC in 19. Stage‐based median overall survival was 26 months for IVA, 44 for IVB, and 29 for IVC. The median PFS was 18, 22 and 21 months for stages IVA, IVB and IVC, respectively. Conclusion: Based on our findings, EBRT may still play a role in the management of patients with thyroid carcinoma and should be considered in the armamentarium against thyroid cancers.